The Influence of the Work Environment and Compensation on the Performance of Employees at the Surya Market Regional Company, Surabaya City - Perdana, Thirafi Putra; Rini, Hesty Prima (PT Inovasi Pratama Internasional, 2024)
This research aims to examine the influence of the work environment and compensation on the performance of employees of the Surya Market Regional Company, Surabaya City. The research method used is quantitative. The population in this study were all employees of the Surya Market Regional Company, Surabaya City, totaling 43 employees. The sampling technique uses a saturated sampling method. Data collection was carried out through distributing questionnaires, while the data analysis technique used SEM PLS with Smart PLS software. The results of this research indicate that the work environment has a contribution to the performance of employees of the Surya Market Regional Company, Surabaya City. This is demonstrated by the work environment variance having a positive and significant effect on the performance of employees of the Surya Market Regional Company, Surabaya City. Meanwhile, compensation does not contribute to the performance of employees of the Surabaya City Surya Market Regional Company. This is demonstrated by the compensation variable which has no significant effect on the performance of the employees of the Surya Market Regional Company, Surabaya City.